The Relationship Between Antimicrobial Activities and Mineral Contents of Narrow Endemic Gypsophytes and Their Chemical Contents - Özdeni̇z, Ebru; Akça, Hanife; Taban, Süleyman; Güney, Kerim; Gür, Mahmut; Özkan, Osman Emre; Kesbi̇ç, Fevziye; Kurt, Latif (Kastamonu University, 2022)
Aim of study: In this study, the relationship between the antimicrobial activities and mineral contents of 7 narrow endemic gypsophyte plant species growing in extreme habitats was investigated. In addition, GC-MS analyzes of these species were also performed.
Material and methods: For this purpose, macro and micro element concentrations in soil and plant and antimicrobial activity against 13 bacteria and one yeast strain were determined by disc diffusion method in 30, 45 and 75 μL methanol and ethyl acetate extracts.
Main results: It has been presented that there is a strong antimicrobial effect potential in these gypsophyte plants. In all plant species taken, it was determined that the total Ca element among the macro elements accumulated more in the plant body than the other macro elements, and it was determined that Fe element accumulated the most among the micro elements. It was assumed that there might be a linear relationship between the strong antimicrobial activity detected in gypsophilic plant species adapted to extreme conditions and the Ca and Fe content.
Highlights: Extramophiles plants could be used in the development of antimicrobial agents in pharmaceutical industry.
Keywords: Antimicrobial Activity; Gypsopyhte; Mineral Content; Narrow Endemic; Antimikrobiyal Aktivite; Jipsofit; Mineral Konsantrasyonu; Dar Yayılışlı Endemik; 15. Life on land